Optic nerve head topography and retinal structural changes in eyes with macrodisks: a comparative study with spectral domain optical coherence tomography - Ozturker ZK (Dove Medical Press, 2016)
Zeynep Kayaarasi Öztürker, Kadir Eltutar, Belma Karini, Sezin Özdogan Erkul, Özen Ayrancı Osmanbaşoğlu, Pınar Sultan Ophthalmology Department, Istanbul Research and Training Hospital, Istanbul, Turkey Purpose: To compare optic nerve head parameters, the thicknesses of the peripapillary retinal nerve fiber layer (pRNFL), the macular retinal nerve fiber layer (mRNFL), the ganglion cell complex (GCC), and the ganglion cell–inner plexiform layer (GCIPL) in macrodisks and normal-sized healthy disks using spectral domain optical coherence tomography. Patients and methods: A total of 88 healthy eyes (42 macrodisks and 46 normal-sized disks) were prospectively enrolled in the study. Optic nerve head parameters as well as pRNFL, mRNFL, GCC, and GCIPL thicknesses were measured in all subjects. Optic disk areas (ODAs) >2.70 mm2 were defined as macrodisks. All spectral domain optical coherence tomography parameters were compared between normal-sized disks and macrodisks. Results: The mean age of the participants was 49.4±5.7 years in the normal size group and 51.55±6.3 years in the macrodisk group (P=0.65). The average ODAs were 2.23±0.29 mm2 and 3.30±0.59 mm2 in the normal size and the macrodisk groups, respectively. ODA (P<0.001), cup area (P<0.001), cup disk area ratio (P<0.001), horizontal cup disk ratio (P<0.001), vertical cup disk ratio (P<0.001), horizontal disk diameter (P<0.001), vertical disk diameter (P<0.001), and cup volume (P<0.001) were significantly higher in the macrodisk group. The inferior mRNFL thickness was significantly lower (P=0.042), and the GCC inferior and GCIPL inferior thicknesses were found to be lower with low significance (P=0.052, P=0.059, respectively) in the macrodisk group. Rim volume (P=0.622), total pRNFL (P=0.201), superior pRNFL (P=0.123), inferior pRNFL (P=0.168), average macular thickness (P=0.162), total mRNFL (P=0.171), superior mRNFL (P=0.356), total GCC (P=0.080), superior GCC (P=0.261), total GCIPL (P=0.214), and superior GCIPL (P=0.515) thicknesses were similar in both groups. Conclusion: Optic disk topography and retinal structures show different characteristics in healthy eyes with macrodisks. These disk size-dependent variations suggest that large optic disks may be more susceptible to glaucomatous damage. Keywords: macrodisk, optic nerve head, nerve fiber layer, ganglion cell complex